PERBEDAAN PENGARUH TERAPI SINAR INFRA MERAH DAN BACK EXERCISE TERHADAP NYERI PUNGGUNG BAWAH - Eko Budi Prasetyo (Universitas Widya Husada Semarang, 2018)
The purpose of this study to determine differences in the effect of back exercisesto increase flexibility of the spine, the lower back pain and spinal flexibility, andto investigate the interaction between type of therapy , low back pain.Type ofresearch is that the study is a quasi-experimental, with a pretest - posttest designapproach . With the method of taking samples is purposive incidental samplingthrough inspection procedures to establish the diagnosis of lower back pain.Theresults in this study are reduction in lower back pain and increase spinal flexibilitybut there is no effect and a significant interaction between the type of physicaltherapy to increase flexibility and decrease lower back pain , then there is nosignificant difference between the type of therapy to lower back pain. Based onthe conclusions obtained the following results : The type of physical therapyinfrared and william flexi exercise compared with other types of physical therapyinfrared and Mc . Kenzie exercise.